A comparative analysis of the determinants of profitability of commercial and microfinance banks in Nigeria - Tosin, Ige Olaoluwa; Otonne, Adewumi (Goodwood Publishing, 2019)
Purpose: The study aims to examine the determinants of profitability of commercial and microfinance banks in Nigeria, in order to be able to highlight the possible effect of Central Bank of Nigeria policy actions in influencing the internal factors and subsequently the profitability of the banks in Nigeria. Research methodology: The study adopted the panel data research design. Out of the total number of 22 commercial banks and 898 microfinance banks the study sampled 4 commercial banks and 4 microfinance banks using random sampling technique, and based on the availability of data. Data were sourced from the annual balance sheets and income statement of banks from 2010 to 2018 and analysed using the Random Effect Panel Estimation Technique. Finding: Findings from the study show that liquidity ratio is not a strong determinant of banks profitability whether commercial or microfinance banks while capital adequacy is a significant determinants of the profit level in both banks with positive effect for microfinance and negative effect for commercial banks. The study also found that real GDP is a significant determinant of only commercial banks profitability. This by implication indicates that the recent policy action by the central bank which saw the increase of cash reserve ratio from 22.5% to 27.5% is expected to have an insignificant reduction on the profitability of the banks. Limitation: The major limitation of the study is the use of a single measure of profitability and a single measure of external factor. The study period as well as its sample size was also considered as limitation. Contribution: Findings from this study are useful to the management of the banks, the selected banks to be more specific, and shareholders. Also, this study provides insights on the possible effect of the recent policy of the Central Bank on the banking sector. Thus, the results of this study are useful to policy makers and regulators of the financial system in Nigeria. Keywords: Profitability, Commercial Bank, Microfinance Banks, Liquidity Ratio, Capital Adequacy, Return on Asset, Real GDP